CLASSIFICATION OF CHILDREN WITH INCOMPLETE SPEECH DEVELOPMENT (Neo Scientific Peer Reviewed Journal, 2026)
This topic examines the classification of children with underdeveloped speech, focusing on the nature, causes, and degrees of speech impairment. It highlights the main groups of speech disorders, including phonetic-phonemic underdevelopment, general speech underdevelopment, and delayed speech development. The classification helps specialists identify the specific characteristics of each type of speech disorder and choose appropriate corrective and pedagogical strategies. Understanding these classifications is essential for effective speech therapy, early intervention, and the development of individualized educational programs for children with speech impairments.